Calculation of property contour diagrams. (December 2016) - Chen, Shuanglin; Cao, Weisheng; Zhang, Chuan; Zhu, Jun; Zhang, Fan; Li, Qian; Zhang, Jieyu
Abstract: Contour diagrams are very useful for describing how a property changes with other variables. One such a diagram is the isothermal lines on a liquidus projection, which helps us understand how the liquidus surface changes with temperature and composition. A method has been implemented in Pandat to calculate two-dimensional property contour diagrams in multi-component systems. Property contour diagrams will be presented for various thermodynamic and physical properties such as phase fraction, partial pressure, molar volume, and driving force.